Kewenangan Mahkamah Pidana Internasional (ICC) dalam Mengeluarkan Surat Perintah Penangkapan terhadap Non-Anggota Statuta Roma: Studi Kasus Perintah Penangkapan Benjamin Netanyahu (The International Criminal Court (ICC) Jurisdiction: Arrest Warrants Beyond Rome Statute States, a Netanyahu Analysis) - Maulana, Adrian; Damanyanti, Ratih; Maskur, Muhammad Azil (Universitas Negeri Semarang, 2025)
Armed conflict has driven the evolution of International Humanitarian Law (IHL) to minimize suffering, yet severe violations persist, necessitating effective enforcement mechanisms like the International Criminal Court (ICC), established by the Rome Statute in 1998. The ICC holds jurisdiction over individuals responsible for genocide, crimes against humanity, war crimes, and the crime of aggression. This article analyzes the ICC's jurisdiction over non-member states of the Rome Statute and the validity of the warrant of arrest issued against leaders from such states, specifically Benjamin Netanyahu, Prime Minister of Israel. Although Israel is not a state party, the ICC can assert jurisdiction if the alleged crimes occurred in the territory of a state party or if the situation is referred by the UN Security Council, in line with the principle of complementarity. The issuance of the warrant of arrest against Netanyahu on May 20, 2024, was based on Article 58 of the Rome Statute following alleged war crimes and crimes against humanity in Gaza, a territory of Palestine (a state party to the Rome Statute), providing a strong legal basis. However, its implementation faces political challenges and rejection from some member states, which could violate their obligations under Article 86 of the Rome Statute.